Proceedings of the 31st Symposium Design for X (DFX2020) 2020
DOI: 10.35199/dfx2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Potentiale datengestützter Methoden zur Gestaltung und Optimierung mechanischer Fügeverbindungen

Abstract: Due to the increasing requirements on lightweight constructions, the demands for efficient joining processes are constantly rising. Therefor cold forming processes provide a faster and less expensive alternative to established thermal joining methods. In order to guarantee the joining reliability, not only the selection of a suitable process, but also the design and dimensioning of the joint is crucial. As a possible solution, data-driven methods offer procedures for the structuring of data and the targeted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Due to the increasing complexity of multidimensional distributions, experimental studies are only applicable for a limited number of parameter variations. Nevertheless, to enable the identification of optimal joint connections, the application of parametric studies in combination with data-based methods already showed high potentials for the analysis of a wide range of different tool geometries (Zirngibl et al, 2020). However, machine learning methods like artificial neural networks (ANN) often require a sufficiently high amount of data.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing complexity of multidimensional distributions, experimental studies are only applicable for a limited number of parameter variations. Nevertheless, to enable the identification of optimal joint connections, the application of parametric studies in combination with data-based methods already showed high potentials for the analysis of a wide range of different tool geometries (Zirngibl et al, 2020). However, machine learning methods like artificial neural networks (ANN) often require a sufficiently high amount of data.…”
Section: Introductionmentioning
confidence: 99%
“…This mainly involves the adjustment and optimization of particular clinching tool and process parameters to maximize quality-relevant geometrical joint characteristics, such as the neck and interlock thickness. For this, the implementation of machine learning methods in combination with a genetic algorithm (GA) showed already a high applicability to determine a solution space involving a wide range of possible design alternatives [3]. Since this mainly requires the definition of a sufficient amount of training data, it is often time-and cost-intensive to setup powerful metamodels and thus to achieve a desired prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Consequently, the adjustment of design or process parameters often requires high time-and cost-intensive development iterations. Therefore, data-based methods provide high potentials for the optimization of target features [3]. However, for the efficient application of techniques like artificial neural networks, a sufficiently large amount of data is often required.…”
mentioning
confidence: 99%